La Quarantaine à Malte aux XVIIe et XVIIIe siècles dans les mémoires, journaux et récits de quelques voyageurs - Depasquale, Carmen (The Northern Mariner / Le marin du nord, 2009)
French Travel Literature, Memoirs and Diaries on Quarantine in Malta, Seventeenth to early Nineteenth centuries Malta, a tiny island in the middle of the Mediterranean Sea, dependent on sea commerce and therefore particularly vulnerable to contagious diseases, had every reason to ensure that strict health regulations concerning the entry of persons and vessels were drawn up and respected. The rigorousness of this regime is perhaps not surprising when one considers that from 1530 to 1798 the rulers of the Maltese archipelago were the Hospitaller Knights of St. John. Travellers spent a varying period of time, depending on their place of departure, in quarantine on Manoel Island. This article undertakes to study the reaction of travellers to these precautions, analysing their impressions and descriptions of how these days in quarantine were spent, limiting itself to authors who chose the French language as the medium of their travelogues, memoirs or diaries.